An assessment framework for adult learners with learning disabilities in post-school education and training - Moodley, Susheila (University of the Free State, 2018)
This study was conducted with a focus on the two broad areas of interest that I have as a practitioner in the field of adult education and training, i.e. assessment practices in PSET institutions and the effect of these assessment practices, specifically on the learning and learning achievement of adult learners with learning disabilities. It can be assumed that most adult learners with learning disabilities in PSET environments are most probably subjected to learning, teaching and assessment practices that cater for learners without significant learning disabilities. Therefore, current assessment practices in the PSET environment may not provide an equitable opportunity for adult learners with learning disabilities to demonstrate the learning outcomes achieved against the set standards. It was therefore necessary to investigate the experiences and perceptions of adult learners with learning disabilities and their lecturers/facilitators/instructors of the current assessment practices in PSET programmes, and if the practices are not appropriate, to investigate how the relevant learners’ achievement of the same learning outcomes and set standards might be assessed in alternative, inclusive and more equitable ways. The study focused on achieving the following four objectives: 1. To investigate the possible positive and negative effects of assessment practices and concessions reported in literature, on adult learners with learning disabilities’ ability to demonstrate their competence against minimum standards. 2. To investigate how adult learners with learning disabilities’ in PSET experience and perceive the assessment practices they are currently subjected to, and how these practices influence their learning and ultimate achievement. 3. To determine how the facilitators/lecturers/instructors of adult learners with learning disabilities in PSET experience and perceive the assessment practices they use to assess their learners with learning disabilities, including the effect that they believe their practices might have on these learners’ learning and ultimate achievement. 4. To compile and validate an assessment framework that will optimally cater for the needs of adult learners with learning disabilities in PSET. The literature review informed the initial empirical study as well as the assessment framework that was finally compiled, evaluated and validated by a panel of purposively selected experts. The empirical phase of the research was mixed methods in nature and used a multipronged data gathering strategy. The first phase of data collection included a survey questionnaire using open-ended questions posed to the two participant groups, i.e. currently enrolled adult learners with learning disabilities and their lecturers/facilitators/instructors. The second phase of the data gathering involved focus groups and one-on-one interviews with some of these learners, their lecturers/facilitators/instructors as well as two specialists. Finally, the integration of these collected data and the literature study findings was done by comparing and converging these data to compile a proposed assessment framework for assessing adult learners with learning disabilities in a PSET environment. The proposed framework was presented to the panel of experts for their evaluation and validation, using a survey questionnaire that allowed this participant group to rate all the features and sub-features of the proposed framework. The data gathered in this phase was then used to amend and finalise the assessment framework, which is the final outcome of this research study. As pragmatist, the value of the study lies in the practical aspect that the framework offers, i.e. the opportunity to use the assessment framework as a vantage point for the development of an inclusive assessment environment that has the ability to improve the assessment experiences of adult learners with learning disabilities by providing practitioners and policy makers with practical tools to realise their inclusion agenda.
Thesis (Ph.D. (Higher Education Studies))--University of the Free State, 2018
Keywords: Assessment; Learning disability; Adult learning; Post-school education and training; Inclusive education; Inclusive assessment; Assessment concessions; Teaching and learning practices aligned to learning disability; Assessment practices; Alternative assessment practices; Innovative assessment practices